Communication failures in the operating room: an observational classification of recurrent types and effects. Issue 5 (1st October 2004) - Lingard, L; Espin, S; Whyte, S; Regehr, G; Baker, G R; Reznick, R; Bohnen, J; Orser, B; Doran, D; Grober, E
Abstract : Background: Ineffective team communication is frequently at the root of medical error. The objective of this study was to describe the characteristics of communication failures in the operating room (OR) and to classify their effects. This study was part of a larger project to develop a team checklist to improve communication in the OR. Methods: Trained observers recorded 90 hours of observation during 48 surgical procedures. Ninety four team members participated from anesthesia (16 staff, 6 fellows, 3 residents), surgery (14 staff, 8 fellows, 13 residents, 3 clerks), and nursing (31 staff). Field notes recording procedurally relevant communication events were analysed using a framework which considered the content, audience, purpose, and occasion of a communication exchange. A communication failure was defined as an event that was flawed in one or more of these dimensions. Results: 421 communication events were noted, of which 129 were categorized as communication failures. Failure types included "occasion" (45.7% of instances) where timing was poor; "content" (35.7%) where information was missing or inaccurate, "purpose" (24.0%) where issues were not resolved, and "audience" (20.9%) where key individuals were excluded. 36.4% of failures resulted in visible effects on system processes including inefficiency, team tension, resource waste, workaround, delay, patient inconvenience and procedural error. Conclusion: Communication failures in the OR exhibited a common set of problems. They occurred in approximately 30% of team exchanges and a third of these resulted in effects which jeopardized patient safety by increasing cognitive load, interrupting routine, and increasing tension in the OR.